Physical Modeling of Dislocation Connection in LEDs under Different External Impacts; Instruments and Experimental Techniques; Vol. 64, iss. 5 - Gradoboev A. V. Aleksandr Vasilyevich; Orlova K. N. Kseniya Nikolaevna; Simonova A. V. Anastasiya Vladimirovna; Sednev V. V. Vyacheslav Vladimirovich (2021, 2021)
Title screen